2010
DOI: 10.1016/j.bbalip.2010.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal lipid alterations occur prior to antibody-induced prostaglandin E2 production in a mouse model of ischemia/reperfusion

Abstract: Original article can be found at: http://www.sciencedirect.com/science/ Copyright Elsevier [Full text of this article is not available in the UHRA]Ischemia/reperfusion (IR) induced injury results in significant tissue damage in wild-type, but not antibody-deficient, Rag-1???/??? mice. However, Rag-1???/??? mice sustain intestinal damage after administration of wild-type antibodies or naturally occurring, specific anti-phospholipid related monoclonal antibodies, suggesting involvement of a lipid antigen. We hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 41 publications
(59 reference statements)
3
29
0
Order By: Relevance
“…Previous studies indicated that the appropriate Ab repertoire is required for recognition of IR-induced neoantigens, complement activation, and eicosanoid production (14, 37). Importantly, TLR4 was not required for production of the appropriate Ab repertoire to induce damage in Ab-deficient, IR-resistant, Rag-1−/− mice (8, 14, 37) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicated that the appropriate Ab repertoire is required for recognition of IR-induced neoantigens, complement activation, and eicosanoid production (14, 37). Importantly, TLR4 was not required for production of the appropriate Ab repertoire to induce damage in Ab-deficient, IR-resistant, Rag-1−/− mice (8, 14, 37) .…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, TLR4 was not required for production of the appropriate Ab repertoire to induce damage in Ab-deficient, IR-resistant, Rag-1−/− mice (8, 14, 37) . To determine if TLR2 −/− mice have the proper Ab repertoire, we injected Rag-1 −/− mice with sera or Ig purified from C57Bl/6 or TLR2 −/− mice and subjected the mice to IR.…”
Section: Resultsmentioning
confidence: 99%
“…Several in vivo studies have documented increased PGE 2 production in response to intestinal IR [13, 2529]. While increased transcription of the Cox enzymes begins during the ischemic period, reperfusion is necessary for PGE 2 production [27]. Endothelial cells produce prostaglandins (reviewed in [22]); however, not all endothelial cells generate the same prostaglandin profile.…”
Section: Ischemia/reperfusionmentioning
confidence: 99%
“…Rag-1 −/− mice do not produce antibodies and do not sustain IR damage; however, administration of pooled wildtype antibodies as well as the IgM fraction alone results in intestinal damage similar to that seen in wildtype animals [27, 55]. It was later shown that human IgM can also elicit injury and complement deposition in Rag-1 −/− and Rag -2 −/− mice [56, 57].…”
Section: Antibodies and Neo-antigensmentioning
confidence: 99%
“…58) On the other hand, the production of LPC was suggested not to be involved in intestinal injury after ischemia and reperfusion stress in mice, but rather production of prostaglandin E 2 participated in the intestinal damage. 59) At high concentrations LPC impaired the mucosal barrier function and increased gastrointestinal permeability in isolated rat ileum, 60) rat stomach, 61) rat intestine, 62) guinea-pig proximal jejunum 63) and human intestinal cells. 64) Intraduodenally injected lipopolysaccharide induced the release of sPLA 2 , increasing the luminal level of LPC in rats, 52) although LPC was found to be protective when injected intravenously in rats.…”
Section: Does Lpc Exert Gastrointestinal Mucosa-injuring or Protectinmentioning
confidence: 99%